Reading Comprehension Skills in EFL Students - Nussy, Wenssy Steva; Pekpekay, Noni (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2024)
This study explores reading comprehension skills among English as a Foreign Language (EFL) students, identifying obstacles and solutions specific to students in semesters two and four of the English Education Study Program at PSDKU ARU. The research involved 22 participants from the 2022-2023 academic year. Data were gathered through questionnaires and interviews, both of which were administered to the students. The purpose was to identify the challenges these students face in their reading comprehension and to examine the strategies employed by lecturers to address these issues. By highlighting the main obstacles and the corresponding solutions, this study aims to enhance understanding and provide insights into improving EFL students' reading comprehension skills.